Lexico-Semantic Features of Tourist Discourse (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article is dedicated to the study of the lexico-semantic features of tourist discourse. Tourism is one of the most dynamically developing sectors of the economy, and the language used in the tourist context plays a key role in shaping the perception of tourist services and in communication between tourists, tourism professionals, and local residents.The main focus of this work is the analysis of specialized terminology, polysemy (the multiplicity of word meanings), metaphors, and figurative expressions, as well as the influence of cultural and sociolinguistic factors on tourist language. The study also examines the impact of digital technologies and social media on the evolution of tourist discourse, which, with the development of the internet, has undergone significant changes, including the emergence of new words and expressions.The aim of the research is to identify the main lexico-semantic features that characterize tourist discourse and to demonstrate how language is used to create attractive images of tourist products and services. The paper emphasizes the importance of understanding these features for effective communication in the tourism sector and improving the quality of customer service.The study demonstrates that tourist discourse is not only an important tool in the field of tourism but also a significant cultural phenomenon reflecting global changes in society and language.